Metodología: discusión y debate como diálogo de saberes para el aprendizaje de Biología con estudiantes de Segundo Año de B.G.U de la Unidad Educativa ¨Juan de Velasco¨ - Vergara Guananga, Andrea Veronica (2024)
The main axis of this research is the discussion and debate methodology as a dialogue of knowledge to enrich the educational experience by promoting active participation. The objective of the study is to argue the importance of the methodology: discussion and debate as a dialogue of knowledge, through the analysis of information and data collection for the learning of Biology with second-year B.G.U students of the "Juan de Velasco¨ Institution. The applied methodology has a quantitative approach with a nonexperimental research design with a descriptive and explanatory level of scope, bibliographic, and field type. The study population is estimated at 35 students distributed between 15 men and 20 women in the second year of B.G.U from the ¨Juan de Velasco¨ Institution in Biology subject. The instrument applied was a survey of 10 closed multiplechoice questions that allowed us to determine the degree of acceptance of the methodology and the Teaching Guide. The results indicate that discussion and debate improve the learning of Biology with a high degree of acceptance because of the Didactic Guide, an interactive tool to help strengthen the learning of Biology. In conclusion, the essential methodology in the construction of knowledge and improving the learning skills of Biology, therefore, the recommendation is to encourage the use of discussion and debate as a dialogue of knowledge.